Oleanolic Acid Diminishes Liquid Fructose-Induced Fatty Liver in Rats: Role of Modulation of Hepatic Sterol Regulatory Element-Binding Protein-1c-Mediated Expression of Genes Responsible for De Novo Fatty Acid Synthesis - Liu, Changjin (Hindawi Publishing Corporation, 2013)
Oleanolic acid (OA), contained in more than 1620 plants and as an aglycone precursor for naturally occurred and synthesized triterpenoid saponins, is used in China for liver disorders in humans. However, the underlying liver-protecting mechanisms remain largely unknown. Here, we found that treatment of rats with OA (25 mg/kg/day, gavage, once daily) over 10 weeks diminished liquid fructose-induced excess hepatic triglyceride accumulation without effect on total energy intake. Attenuation of the increased vacuolization and Oil Red O staining area was evident on histological examination of liver in OA-treated rats. Hepatic gene expression profile demonstrated that OA suppressed fructose-stimulated overexpression of sterol regulatory element-binding protein-(SREBP-) 1/1c mRNA and nuclear protein. In accord, overexpression of SREBP-1c-responsive genes responsible for fatty acid synthesis was also downregulated. In contrast, overexpressed nuclear protein of carbohydrate response element-binding protein and its target genes liver pyruvate kinase and microsomal triglyceride transfer protein were not altered. Additionally, OA did not affect expression of peroxisome proliferator-activated receptor-gamma- and -alpha and their target genes. It is concluded that modulation of hepatic SREBP-1c-mediated expression of the genes responsible for de novo fatty acid synthesis plays a pivotal role in OA-elicited diminishment of fructose-induced fatty liver in rats.